Financial Education and its Contribution to Financial Inclusion: An Approach from the School Curriculum - Rozas Villacorta, Leonardo (2024)
The study investigates the impact of the National Curriculum Design implemented in 2009 on financial inclusion, evaluating three dimensions: savings account ownership, savings account ownership and use, and credit card ownership and use. The participants were divided into two groups, those who followed the 2009 curriculum and those who did not, analyzing the gap between them before and after implementation. The Propensity Score Matching method was implemented with Probit regression and matching using the Kernel method. Data from the 2015 Peruvian National Household Survey were used to evaluate the immediate impact, extending to the years 2017, 2019 and 2021 to measure the impact over time. The results indicate a significant positive impact of long-term financial education on the three dimensions of financial inclusion. This suggests that policies of this type do not generate immediate impact, but are developed progressively